Does product involvement influence how emotions drive satisfaction?: An approach through the Theory of Hedonic Asymmetry - Cristina Calvo-Porral; Agustín V. Ruiz Vega; Jean-Pierre Lévy Mangin (European Research on Management and Business Economics (ERMBE), 2018)
This study examines whether the level of product involvement influences how emotions drive consumer satisfaction. Based on the Theory of the Hedonic Asymmetry we analyze through Structural Equation Modeling (SEM) how emotions drive consumer satisfaction. A sample of 570 respondents was gathered for a high involvement product – wine –, while a sample of 431 consumers was collected for a low involvement product – a cup of coffee –. Results show that positive emotions exert a higher influence on satisfaction in low involvement products, rather than in high involvement products, suggesting that situational factors – such as the occasion of consumption – could be acting as qualifiers of pleasant emotions. Additionally, our findings support the moderating role of product involvement on the consumption-elicited emotions and satisfaction link.
Keywords: 650; Involvement; Emotions; Satisfaction